Location choices of multinational companies in Ukraine - Daria Zvirgzde; Daniel Schiller; Javier Revilla Diez (European Regional Science Association (ERSA), 2013)
There has been a wide acknowledgement of the role of foreign direct investment (FDI) for economic growth and development of states, regions and cities. Special attention has been paid to FDI flows to transition economies, which owe their economic and social transformation to a large extent to multinational companies (MNCs) which introduce knowledge, technology and new opportunities into these emerging markets. FDI flows from developed countries towards emerging economies becomes an important transmitter of economic resources and serves as a catalyst for development and attraction of further investments. While the role of FDI for economic growth of countries has been discussed quite comprehensively in the literature, the regional level and the factors behind the geographical distribution of FDI at the sub-national level have not gained sufficient attention. The factors that attract MNCs towards certain markets and economies are unevenly distributed among countries and regions. The range of specific host region determinants for the attraction of FDI is generally divided into two broad groups: traditional economic factors and institutional factors. Traditional economic factors are based on the systematic conceptualisation of FDI location choices by Dunning (1993) in his eclectic paradigm OLI, which stands for ownership, location and internalisation advantages. The relevance of the institutional perspective for location choices of MNCs has gained a much wider audience recently. It focuses explicitly on the embeddedness of firms into local institutional environments. Foreign firms become highly dependent on the institutional factors at the chosen location for investment and have to adapt themselves (at least to a certain degree) to the local institutional framework in order to gain legitimacy and integration within the regional economic system. The aim of the paper is to identify determinants of location choices of FDI in transition economies, based on empirical evidence of an enterprise survey carried out in three regions in Ukraine within the project ?SEARCH: Sharing knowledge assets: interregionally cohesive neighbourhoods? funded by the European Union within the Seventh Framework Programme for Research (FP7). By and large, the paper contributes to the provision of a thorough theoretical framework on location choices of MNCs by integrating the institutional component and provides empirical results on (1) traditional economic factors that attract FDI to certain localities within transition economies, specifically Ukraine and (2) institutional and proximity parameters of regions that attract or distract MNCs in order to determine the impact of the institutional environment and proximity advantages of certain regions on the propensity of foreign firms to invest in certain regional host markets.
Keywords: D23; F21; F23; R11; 330; Location determinants; FDI; multinational company; transition economy; enterprise survey